$\displaystyle y = \frac{4}{3}x^{\frac{3}{4}-\pi} $

$\displaystyle ln(y) = ln(\frac{4}{3}x^{\frac{3}{4}-\pi}) $

$\displaystyle ln(y) = ({\frac{3}{4}-\pi})ln(\frac{4}{3}x) $

$\displaystyle \frac{1}{y}\frac{dy}{dx} = (\frac{3}{4}-\pi(\frac{d}{dx}(ln(\frac{4}{3}x)))) $

$\displaystyle \frac{1}{y}\frac{dy}{dx} = (\frac{3}{4}-\pi)(\frac{3}{4}x)*(\frac{4}{3}) $

$\displaystyle \frac{dy}{dx} = y(\frac{3}{4}x-\pi(x)) $

$\displaystyle \frac{dy}{dx} = \frac{4}{3}x^{\frac{3}{4}-\pi}(\frac{3}{4}x-\pi(x)) $